2020
DOI: 10.3390/w12020360
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Vulnerability Assessment Due to Sea Level Rise: The Case Study of the Atlantic Coast of Mainland Portugal

Abstract: Sea level rise, a consequence of climate change, is one of the biggest challenges that countries and regions with coastal lowlands will face in the medium term. This study proposes a methodology for assessing the vulnerability to sea-level rise on the Atlantic coast of mainland Portugal. Some scenarios of extreme sea levels for different return periods and extreme flooding events were estimated for 2050 and 2100, as proposed by the European Directive 2007/60/EC. A set of physical parameters are considered for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 40 publications
(66 reference statements)
0
13
0
3
Order By: Relevance
“…Compared with conventional solutions, it has a lower potential environmental impact, uses local materials and has the possibility of being moved or disassembled and relocated. Studies on coastal vulnerability and flooding assessment due to sea level rise [56,57] concluded that it is evident that inland waters, as the Ria de Aveiro estuary (with an arm connecting to the Praia de Mira lagoon), will be the most affected areas, corresponding also to an area with a high level of exposure of people and buildings. These studies evaluated the risk for 2025, 2050 and 2100 with different sea-level scenarios and different extreme event return periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional solutions, it has a lower potential environmental impact, uses local materials and has the possibility of being moved or disassembled and relocated. Studies on coastal vulnerability and flooding assessment due to sea level rise [56,57] concluded that it is evident that inland waters, as the Ria de Aveiro estuary (with an arm connecting to the Praia de Mira lagoon), will be the most affected areas, corresponding also to an area with a high level of exposure of people and buildings. These studies evaluated the risk for 2025, 2050 and 2100 with different sea-level scenarios and different extreme event return periods.…”
Section: Discussionmentioning
confidence: 99%
“…The area of Praia de Mira is not an exception, showing high risk in some parts as early as in 2025 and increasing considerably in the scenarios for 2050 and 2100. The vulnerability and the risk of coastal areas represent considerable potential negative social and economic impacts [57]. Therefore, the implementation of timely adaptation measures is needed to minimize the impacts and the exponential costs associated, since the time required to study, design and implement these measures will be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Global warming is expected to significantly increase coastal vulnerability due to potential changes in precipitation patterns, floods and of marine storms intensities 35 . Our results suggest that the arid deltaic and sandy beaches of the North African coasts are among the most vulnerable to disturbances from coastal hazards in the central and eastern Mediterranean Basin.…”
Section: Origins and Implications Of The Coastal Vulnerabilitymentioning
confidence: 99%
“…Moreover, it has been estimated that 900 km 2 of the Portuguese coast could be subject to flood risk in 2050, considering 50 year return period extreme events and empirical sea-level rise projections. At the end of the century, the areas at risk of coastal flooding could increase by 27%, where Lisbon, Faro and Aveiro are the districts most at risk [37,38].…”
Section: The Impacts Of and Adaptation To Sea-level Rise In The Iberian Peninsulamentioning
confidence: 99%